PENGARUH PENGUNGKAPAN EMISI GAS RUMAH KACA DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Lestasi, Delisa; Baihaqi, Baihaqi (Universitas Riau, 2026)
This study examines the effect of greenhouse gas emission disclosure and environmental performance on firm value from the perspective of signaling theory. The research focuses on mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Firm value is proxied by Tobin’s Q, greenhouse gas emission disclosure is measured using a content analysis–based disclosure index, and environmental performance is represented by the PROPER rating. Panel data are analyzed using multiple linear regression. The results indicate that greenhouse gas emission disclosure has a positive and significant effect on firm value, suggesting that emission disclosure serves as a credible sustainability signal for investors. In contrast, environmental performance measured through PROPER does not significantly affect firm value, indicating that compliance-based environmental indicators have limited signaling power in capital markets. Financial control variables, including profitability, leverage, and firm size, function as control factors in explaining firm value. This study contributes to the signaling theory literature by highlighting that different types of environmental signals possess varying strengths in influencing firm value, particularly in the context of emerging capital markets. The findings also provide insights for managers and regulators regarding the importance of enhancing quality of environmental disclosure beyond minimum regulatory compliance